2017
DOI: 10.1158/1055-9965.epi-17-0264
|View full text |Cite
|
Sign up to set email alerts
|

Age at Menarche and Late Adolescent Adiposity Associated with Mammographic Density on Processed Digital Mammograms in 24,840 Women

Abstract: Background High mammographic density is strongly associated with increased breast cancer risk. Some, but not all, risk factors for breast cancer are also associated with higher mammographic density. Methods The study cohort (N=24,840) was drawn from the Research Program in Genes, Environment and Health of Kaiser Permanente Northern California and included non-Hispanic white females aged 40–74 years with a full-field digital mammogram (FFDM). Percent density (PD) and dense area (DA) were measured by a radiolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…Rapid infant weight gain has also been shown to accelerate age at menarche, a risk factor for BC (49,(58)(59)(60)(61)(62). Early age at menarche, however, has been associated with lower MD as seen in a recent study of more than 20,000 women, which is consistent with our finding of rapid infant weight gain lowering MD (63). Earlier age at menarche might be associated with increased BC risk through a pathway that is not mediated by MD (64).…”
Section: Discussionsupporting
confidence: 85%
“…Rapid infant weight gain has also been shown to accelerate age at menarche, a risk factor for BC (49,(58)(59)(60)(61)(62). Early age at menarche, however, has been associated with lower MD as seen in a recent study of more than 20,000 women, which is consistent with our finding of rapid infant weight gain lowering MD (63). Earlier age at menarche might be associated with increased BC risk through a pathway that is not mediated by MD (64).…”
Section: Discussionsupporting
confidence: 85%
“…GE images processed using Tissue Equalization software were retrieved from the KPNC imaging archive, and downsampled from a pixel size of 94 microns to 200 microns. We found that denoising of the GE images did not improve the reproducibility of the density measurements and therefore did not denoise the downsampled images 51 . GE images were randomly assembled into 6 batches of up to 700 images each, including randomly selected replicates for quality control.…”
Section: Methodsmentioning
confidence: 89%
“…Women were excluded if their mammograms contained breast implants (3.6%), did not contain the entire breast (1%), or were unreadable/unavailable (2.6%) 51 . Women with a history of bilateral breast cancer (0.06%) were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Model covariates were chosen a priori based on their established associations with mammographic density in prior studies (6) and included age, BMI, parity (number of children), age at first birth, family history of breast cancer, menopausal status, and use of menopausal hormones within the past 5 years. We included BMI and BMI 2 in the DA model and BMI, BMI 2 , and BMI 3 in the PD model, based on the best model fit as determined by Akaike's Information Criterion (16). Missing covariate data from the survey were imputed using the Markov chain Monte Carlo approach (19).…”
Section: Methodsmentioning
confidence: 99%
“…FFDM mammograms came from 37 different mammography facilities within KPNC, with 1-5 machines per facility. Image selection and exclusion criteria have been described previously (16). Of the 24,840 women in the final cohort, 1,406 women (5.7%) had previously had breast cancer.…”
Section: Mammogramsmentioning
confidence: 99%